Biologging in service of wildlife management: a system for bear dissuasion and reeducation - Ossi, F.; Molteni, D.; Picco, G. P.; Murphy, A.; Avenia, S.; Svaizer, N.; Sforna, T. (country:DE, 2017)
Brown bear (Ursus Arctos) has been successfully reintroduced in Central Alps (Trentino, Italy) in 2000, where the population currently expanded to 50 individuals. Bear presence in a highly anthropized landscape poses significant management challenges to promote coexistence between this species and local stakeholders, such as farmers and beekeepers, as bears may approach and use anthropic resources. Prevention measures represent a crucial element to significantly reduce damages caused by bears. To address these issues, we developed BEARFENCE, an innovative prevention system that aims both at deterring bears and at reeducating confident individual. BEARFENCE consists of i) a base station emitting 125 Khz radio signals; ii) a bear tag mounted on a collar that wakes up once the bear falls within the transmission range of the base station, communicating back with the base station in case of wake-up; iii) a wireless sensor network (WSN) composed of the base station that coordinates several sensors, which in turn trigger the proper deterrents in case of bear attack. The triggering sequence, duration and intensity of the deterrents are randomly coordinated by the base station, with the ultimate goal to minimize the risk of habituation of the bear to the prevention system. Prior to final deployment on bears (ongoing), we extensively evaluated Bearfence performance in the field, under different environmental conditions and application scenarios. We combined ‘in vitro’ tests (i.e., performed by operators that carried tags) and ‘in vivo’ tests (fitting the tags to donkeys). The tests demonstrated the effective functionality of the Bearfence system, with the rate of missed detection of the bear tag close to zero. We encourage wildlife managers to consider Bearfence as a complementary system to prevent bear attacks. We foresee future applications of this system for other mammal of management concern